The Influence of Compensation and Work Motivation on Job Satisfaction of GIG Economy Workers - Yusuf, Raihan Alfarizi; Hasan, Diana (Universitas Muhammadiyah Pontianak, 2026)
The GIG economy, often facilitated by digital platforms, enables part-time work arrangements. This study focuses on online motorcycle taxi drivers in Kebayoran Lama Selatan, who play a vital role in providing delivery and transport services. The research aims to examine the influence of compensation and work motivation on job satisfaction among these workers. Using a quantitative approach, the t-test shows compensation has no significant effect, while work motivation does. However, the F-test indicates both variables together significantly affect job satisfaction. It is recommended to raise driver fares and provide appropriate bonuses to enhance their overall job satisfaction.